Pengaruh Konservatisme Akuntansi dan Capital Intensity Terhadap Tax Avoidance yang Di Moderasi oleh Dewan Komisaris Independen - Elinda Widayu; Lintang Venusita (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the effect of accounting conservatism and capital intensity on tax avoidance which is moderated by an independent board of commissioners. The research sample is a manufacturing company that is listed consistently on the Indonesia Stock Exchange (IDX) in 2020-2022. The research method used in this research is a quantitative method with sampling using a purposive sampling technique, data testing using SPSS 25 software which is analyzed using multiple regression tests and MRA tests. The results of the research conducted show that accounting conservatism has no effect on tax avoidance. Capital intensity has a negative effect on tax avoidance and the independent board of commissioners is unable to moderate it, namely strengthening or weakening the relationship between accounting conservatism and capital intensity on tax avoidance.